Enhancing the Student Experience : Transition from Vocational Education and Training to Higher Education : Final Report. - Catterall, Janice; Davis, Janelle (Australian Learning and Teaching Council (ALTC), 2012)
The continuing increase in students who enter higher education in Australia as a result of their studies in the vocational education and training (VET) sector has led to heightened national interest in the transition experience of these students. Final report from a project that reports on the experiences of students who entered UWS, as a result of their VET studies in 2009 and 2010 in the fields of business, law, nursing and early childhood. The investigation used quantitative and qualitative methods to elicit responses from students about a range of experiences including interaction with administrative procedures and teaching and learning. Approximately 530 students responded to a detailed survey, 40 students engaged in telephone interviews and a further 35 students attended focus groups. In 2011 an extension phase was approved with a focus on the advantages of structured pathways. Overall it was found that the pathways seem to be working well with students welcoming the challenge of new study and life experiences. Students did report some stress in transition related to differences between sectors in areas such as orientation to study, learning styles, academic literacies and assessment. A number of strategies have been piloted and changes have been made to curriculum and assessment strategies. The project has developed a VET transition web page and a UWS site for commencing students making the transition to university. These strategies have been designed to be financially viable and engaging of stakeholders to encourage sustainability. Use of the learning from the project has led to recommendations being progressively funded and adopted.